ENHANCING VICTIM-CENTERED JUSTICE THROUGH RESTITUTION: A FRAMEWORK FOR VICTIM IMPACT STATEMENTS IN CHILD SEXUAL VIOLENCE CASES - Anang Riyan Ramadianto; Milda Istiqomah; Nurini Aprilianda (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines the role of the Victim Impact Statement (VIS) and restitution in safeguarding the rights of child victims of sexual violence within Indonesia’s criminal justice system. The research highlights the importance of VIS in providing victims with a formal avenue to express the physical, emotional, social, and economic impacts of crimes committed against them. The study adopts a normative juridical approach, analyzing statutory regulations and case law to assess the implementation of Supreme Court Regulation (PERMA) No. 1 of 2022. Comparative analysis with legal frameworks from other countries, such as the United States and Australia, underscores the necessity of institutionalizing VIS in Indonesia to align with international best practices. Findings reveal that while PERMA No. 1 of 2022 provides a legal foundation for restitution, significant challenges remain in terms of legal structure, substance, and culture, limiting its effectiveness. The study proposes a standardized VIS model tailored for child sexual violence cases to ensure clarity, consistency, and fairness in judicial decisions. Strengthening the legal framework, providing specialized training, and raising public awareness are crucial steps toward integrating VIS into Indonesia’s justice system. This research contributes to the broader discourse on victim-centered justice, emphasizing the need for systemic reforms to enhance legal protections for child victims.